2020
DOI: 10.1016/j.ijid.2020.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Detection of spleen abscesses facilitates diagnosis of melioidosis in Malaysian children

Abstract: Melioidosis is associated with extremely high case fatality ratios. The aim of this study was to determine whether detection of abdominal visceral abscesses can facilitate diagnosis of melioidosis in children. Methods: We conducted a retrospective analysis of all children who had liver and/or spleen abscesses on abdominal ultrasonography admitted to Bintulu Hospital in Sarawak, Malaysia, from January 2014 until December 2018. Results: Fifty-three children had liver and/or spleen abscesses. Spleen abscesses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This percentage is considerably higher than the 7%-22% in other study cohorts [16][17][18]20]. Hence, bedside ultrasound scan in the acute setting may be helpful in the early detection of melioidosis [22]. We also observed that patients with septic shock tend to develop acute kidney injury, as there were significant differences in serum bicarbonate, urea and creatinine levels.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This percentage is considerably higher than the 7%-22% in other study cohorts [16][17][18]20]. Hence, bedside ultrasound scan in the acute setting may be helpful in the early detection of melioidosis [22]. We also observed that patients with septic shock tend to develop acute kidney injury, as there were significant differences in serum bicarbonate, urea and creatinine levels.…”
Section: Discussionmentioning
confidence: 58%
“…The initial choice of empirical antibiotics for serious febrile illnesses were Cpenicillin and ceftazidime. Bedside ultrasound scans were routinely performed in casualty for early identification of liver or splenic abscesses to confirm the clinical suspicion of melioidosis [22]. We believe that the synergistic effect of early detection of melioidosis with bedside abdominal ultrasonography and initiation of melioidosis antibiotics may be the main reason for the low mortality rate at our centre.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the spleen is the second most affected organ (after the lungs). Interestingly, the spleen was also found to be one of the commonest affected organs in children with melioidosis in this region [ 34 ]. In comparison, splenic abscesses are detected in only 25% and 5% of melioidosis patients in Thailand and Australia, respectively [ 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spleen was the most common organ affected in disseminated infections; occult splenic abscesses were present in 85% (11/13) of children with disseminated disease and in 58% (11/19) overall. As previously reported, detection of splenic abscesses by abdominal ultrasonography offers a useful and rapid clue to melioidosis diagnosis [ 46 ]. In addition, the detection of occult splenic abscesses in children with seemingly localized head and neck melioidosis in this study is also important in view of recent suggestions that localized infections might adequately be treated with oral antibiotics alone [ 21 ].…”
Section: Discussionmentioning
confidence: 89%